Absence of W Chromosome in Psychidae Moths and Implications for the Theory of Sex Chromosome Evolution in Lepidoptera - Hejníčková, Martina (Genes (Basel), 2019)
Moths and butterflies (Lepidoptera) are the largest group with heterogametic females. Although the ancestral sex chromosome system is probably Z0/ZZ, most lepidopteran species have the W chromosome. When and how the W chromosome arose remains elusive. Existing hypotheses place the W origin either at the common ancestor of Ditrysia and Tischeriidae, or prefer independent origins of W chromosomes in these two groups. Due to their phylogenetic position at the base of Ditrysia, bagworms (Psychidae) play an important role in investigating the W chromosome origin. Therefore, we examined the W chromosome status in three Psychidae species, namely Proutia betulina, Taleporia tubulosa, and Diplodoma laichartingella, using both classical and molecular cytogenetic methods such as sex chromatin assay, comparative genomic hybridization (CGH), and male vs. female genome size comparison by flow cytometry. In females of all three species, no sex chromatin was found, no female-specific chromosome regions were revealed by CGH, and a Z-chromosome univalent was observed in pachytene oocytes. In addition, the genome size of females was significantly smaller than males. Overall, our study provides strong evidence for the absence of the W chromosome in Psychidae, thus supporting the hypothesis of two independent W chromosome origins in Tischeriidae and in advanced Ditrysia.